2023
DOI: 10.1021/acs.inorgchem.3c01887
|View full text |Cite
|
Sign up to set email alerts
|

Solution Studies of a Water-Stable, Trivalent Antimony Pnictogen Bonding Anion Receptor with High Binding Affinities for CN, OCN, and OAc

Jinchun Qiu,
Curt N. Bateman,
Shuai Lu
et al.

Abstract: The solution phase anion binding behavior of a waterstable bidentate pnictogen bond donor was studied. A modest change in the visible absorption spectrum allowed for the determination of the binding constants. High binding constants were observed with cyanide, cyanate, and acetate, and these were corroborated with density functional theory (DFT) calculations. The receptor could be recovered free from the anion following treatment with methyl triflate, confirming that it remains intact. The tight binding of cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 83 publications
(174 reference statements)
0
2
0
Order By: Relevance
“…Especially, we are interested in the solvent effect of water due to the fact that ion recognition in aqueous solution is a major challenge in supramolecular chemistry. [42][43][44] Here, the solvent effects of water and toluene are considered. Interestingly, it is found that the structure of EUPR in solvents is quite different from that in gas phase.…”
Section: Geometric Configurationsmentioning
confidence: 99%
“…Especially, we are interested in the solvent effect of water due to the fact that ion recognition in aqueous solution is a major challenge in supramolecular chemistry. [42][43][44] Here, the solvent effects of water and toluene are considered. Interestingly, it is found that the structure of EUPR in solvents is quite different from that in gas phase.…”
Section: Geometric Configurationsmentioning
confidence: 99%
“…Anion binding has also been investigated by the Cozzolino group using oxygen-bridged bidentate distibines 38 such as 14 which displays halide binding constants in CH 2 Cl 2 of 870,000 ± 98,000 M -1 , 16,900 ± 5,000 M –1 , 2,390 ± 1,470 M –1 for chloride, bromide, and iodide, respectively ( Figure 4 ). 39 In addition to showing halide anion binding selectivity, 14 also interacts with the cyanide anion and effectively promotes its phase transfer for applications in cyanation chemistry.…”
Section: Anion Complexation Chemistrymentioning
confidence: 99%